2009
DOI: 10.1186/1471-2466-9-9
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic role of glycosaminoglycans in pleural effusions: A pilot study

Abstract: Background: Pleural effusions are classified into transudates and exudates. Various criteria have been used with Light's et al being the most accepted ones. Glycosaminoglycans (GAGs) have been detected during pleural fluids (PF) analysis in various causes. In this pilot study, we investigated: (a) the usefulness of GAGs in the assessment of pleural effusions, and (b) whether and in what way GAGs correlate with established criteria used to indicate an exudate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…Studies supporting the utility of pleural proinflammatory cytokines during pleural fluid analysis revealed that a low absolute neutrophil count may give a diagnosis of empyema with a sensitivity rate of 78.6% and a specificity rate of 88.4% in the presence of elevated IL-8. Similar findings are reported with IL-1 [ 35 , 36 ].…”
Section: The Promise Of Biological Pleural Markers To Determine Thsupporting
confidence: 91%
“…Studies supporting the utility of pleural proinflammatory cytokines during pleural fluid analysis revealed that a low absolute neutrophil count may give a diagnosis of empyema with a sensitivity rate of 78.6% and a specificity rate of 88.4% in the presence of elevated IL-8. Similar findings are reported with IL-1 [ 35 , 36 ].…”
Section: The Promise Of Biological Pleural Markers To Determine Thsupporting
confidence: 91%
“…Thirdly, further developments in contrast agent “activation” by RF, microwaves, and magnetic fields can extend the applications limited by the minimal depth penetration of optical sources. Currently a few in-human studies have used PA techniques: 1) PA spectroscopy to measure oxygenation levels in hyper- and hypo-ventilating healthy volunteers; 95 2) PA flow cytometry to quantify circulating melanoma cells in a stage IV melanoma patient’s blood sample; 96 and 3) in vivo PAT imaging to examine human breast tumors to visualize tumor vascularity based on optical contrast characteristic of breast tissue. 97, 98 Further developments in instrumentation and evaluation of contrast agents for photoacoustic imaging will move toward a molecular approach in the clinic.…”
Section: Preclinical Developments In Molecular Imaging and Potential mentioning
confidence: 99%
“…Asthma affects approximately 300 million people worldwide and the number is projected to reach 400 million by 2025 [1]. Inhalations of allergen stimulates lung epithelial cells and innate immune cells such as dendritic cells (DC), nuocytes, basophils, mast cells, and macrophages [2-6].…”
Section: Introductionmentioning
confidence: 99%